A Copper‐Catalyzed Tandem C–H ortho‐Hydroxylation and N–N Bond‐Formation Transformation: Expedited Synthesis of 1‐(ortho‐Hydroxyaryl)‐1H‐indazoles. Issue 45 (27th November 2017) - Chen, Cheng‐yi; He, Fengxian; Tang, Guangrong; Ding, Han; Wang, Zhaobin; Li, Dawei; Deng, Lujiang; Faessler, Roger
Abstract : A facile, one‐pot synthesis of 1 H ‐indazoles featuring a Cu‐catalyzed C–H ortho ‐hydroxylation and N–N bond‐formation sequence with the use of pure oxygen as the terminal oxidant was developed. The reaction of readily available 2‐arylaminobenzonitriles with various organometallic reagents led to ortho ‐arylamino N–H ketimine species. Subsequent Cu‐catalyzed hydroxylation at the ortho position of the aromatic ring followed by N–N bond formation in DMSO under a pure‐oxygen atmosphere afforded a wide variety of 1‐( ortho ‐hydroxyaryl)‐1 H ‐indazoles in good to excellent yields. This efficient method does not require the utilization of noble‐metal catalysts, elaborate directing groups, or privileged ligands. Abstract : A Cu‐catalyzed C(sp 2 )–H ortho ‐hydroxylation and N–N bond‐formation sequence is described for the synthesis of 1‐( ortho ‐hydroxyaryl)‐1 H ‐indazoles by using pure oxygen as the terminal oxidant. The ortho ‐arylamino N–H ketimine moiety serves as an effective directing group for C(sp 2 )–H oxidation. acac = acetylacetonate.